2019
DOI: 10.9734/ajess/2019/v5i430159
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Practices Related to Health Education in Moroccan Schools

Abstract: In this study, we are interested in teachers’ practices related to health education (HE) in school. In our survey, we used a questionnaire as an investigative tool with a sample of 300 teachers from three levels of education: Primary, middle and qualifying high schools. According to the teachers' statements, our study reveals that the majority practice HE in class despite having no training in this area. They generally practice it in a thematic approach that is limited to pedagogical sequences within the frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…For example, smoking and bullying could be prevented by implementing various whole-school health interventions, 42 poor mental health may be reduced by “universal resilience-focused interventions (particularly cognitive-behavioral therapy-based approaches),” 43 and specific targeted dietary behaviours could be improved with “specific school food environment policies, such as direct provision of healthful foods/beverages.” 44 In addition, multi-level “hand-washing interventions can reduce the incidence of diarrhoea, respiratory infections, and school absenteeism.” 45 School health promotion has been integrated into the curriculum of the school system in Morocco, yet, in a study most teachers who practiced health education indicated that they had not been trained in health education, and almost all expressed a need for training in health education. 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, smoking and bullying could be prevented by implementing various whole-school health interventions, 42 poor mental health may be reduced by “universal resilience-focused interventions (particularly cognitive-behavioral therapy-based approaches),” 43 and specific targeted dietary behaviours could be improved with “specific school food environment policies, such as direct provision of healthful foods/beverages.” 44 In addition, multi-level “hand-washing interventions can reduce the incidence of diarrhoea, respiratory infections, and school absenteeism.” 45 School health promotion has been integrated into the curriculum of the school system in Morocco, yet, in a study most teachers who practiced health education indicated that they had not been trained in health education, and almost all expressed a need for training in health education. 46 …”
Section: Discussionmentioning
confidence: 99%
“…45 School health promotion has been integrated into the curriculum of the school system in Morocco, yet, in a study most teachers who practiced health education indicated that they had not been trained in health education, and almost all expressed a need for training in health education. 46 Limitations of the study "Secondary education net-enrolment ratio" was 92.3% in Morocco in 2010 and 94.6% in 2016, 47 indicating that some out-of school adolescents were not included in this survey in Morocco. Several study variables were excluded from this analysis, since they were either not assessed in all three waves of the Morocco GSHS or had too many missing values.…”
Section: Dovepressmentioning
confidence: 97%
“…Thus, it is essential to value all three modes of instruction in the content of textbooks [22]- [23]. Within this context, it is clear that the textbook influences teaching practices, lesson content, and the experimental teaching processes [24]- [25].…”
Section: Introductionmentioning
confidence: 99%